Epothilone B Benefits Nigrostriatal Pathway Recovery by Promoting Microtubule Stabilization After Intracerebral Hemorrhage. Issue 2 (18th January 2018) - Yang, Yang; Zhang, Xuan; Ge, Hongfei; Liu, Wei; Sun, Eryi; Ma, Yuanyuan; Zhao, Hengli; Li, Rongwei; Chen, Weixiang; Yuan, Jichao; Chen, Qianwei; Chen, Yujie; et al.
Abstract : Background: Many previous clinical studies have demonstrated that the nigrostriatal pathway, which plays a vital role in movement adjustment, is significantly impaired after stroke, according to medical imaging and autopsies. However, the basic pathomorphological changes have been poorly investigated to date. This study was designed to explore the pathomorphological changes, mechanism, and therapeutic method of nigrostriatal impairment after intracerebral hemorrhage (ICH). Methods and Results: Intrastriatal injection of autologous blood or microtubule depolymerization reagent nocodazole was performed to mimic the pathology of ICH in C57/BL6 mice. Immunofluorescence, Western blotting, electron microscopy, functional behavioral tests, and anterograde and retrograde neural circuit tracking techniques were used in these mice. The data showed that the number of dopamine neurons and the dopamine concentration were severely decreased and that fine motor function was impaired after ICH. Microtubule depolymerization was the main contributor to the loss of dopamine neurons and to motor function deficits after ICH, as was also proven by intrastriatal injection of nocodazole. Moreover, administration of the microtubule stabilizer epothilone B (1.5 mg/kg) improved the integrity of the nigrostriatal pathway neural circuit, increased the number of dopamine neurons (4598±896 versus 3125±355; P =0.034) and the dopamine concentration (4.28±0.99 versus 3.08±0.75 ng/mg; P =0.041), and enhanced fine motor functional recovery associated with increased acetylated α‐tubulin expression to maintain microtubule stabilization after ICH. Conclusions: Our results clarified the pathomorphological changes of the nigrostriatal pathway after ICH and found that epothilone B helped alleviate nigrostriatal pathway injury after ICH, associated with promoting α‐tubulin acetylation to maintain microtubule stabilization, thus facilitating motor recovery.